The mediating roles of buoyancy and boredom in the relationship between autonomous motivation and engagement among Chinese senior high school EFL learners - Wang, Ying; Liu, Honggang (Frontiers in Psychology, 2022)
As one of the most salient topics in individual difference research on second language acquisition, second language motivation studies guided by theories and methods from neighboring fields have been increasing for several decades. Self-determination theory (SDT) (Deci and Ryan, 1985; Ryan and Deci, 2017) is one of the most influential theories to provide a comprehensive framework for investigating language learning motivation (Noels et al., 2020). To date, an array of SDT-related studies has been performed to explore ways to develop more self-determined types of motivation. However, the relationship between self-determined types of motivation and other psychological variables has been less researched. To address this gap, the present study investigated the complex relationships among autonomous motivation, boredom, buoyancy and engagement in a sample of 561 Chinese senior high school English as a foreign language (EFL) learners. The results showed that (1) autonomous motivation directly affected student engagement in EFL learning and (2) autonomous motivation also indirectly affected student engagement in EFL learning through the separate mediation of boredom and buoyancy in EFL learning as well as the chain mediation of both mediators. The results supported the SDT and offered some pedagogical implications for teachers and educators.